Preparation method of oxygen vacancy-rich silver bismuthate / bismuth molybdate heterojunction
By combining BI2MOO6 with AGBIO3 to build Z -type heterogeneous knots to form an Agbio3/BI2MOO6 heterogeneous optical catalyst rich in oxygen -rich space, it solves the problem of low efficiency of the existing photocatalyst at visible light, and achieves efficient photocatalytic degradation degradation degradation. Performance and stability.
Patent Information
- Application Number
- CN202411481028.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
AI Technical Summary
Existing semiconductor photocatalysts have low efficiency in visible light, low efficiency in photogenerated carrier migration and interface reaction, resulting in insufficient stability and activity when degrading pollutants.
By combining Bi2MoO6 with AgBiO3 materials, a Z-shaped heterojunction is constructed to form an AgBiO3/Bi2MoO6 heterojunction photocatalyst rich in oxygen vacancies, which improves the separation efficiency of photogenerated carriers and enhances photocatalytic activity.
It significantly improves the visible optical utilization rate and photocatalytic degradation performance of photocatalysts, improves the degradation efficiency of organic pollutants, and enhances the stability and activity of materials.
Smart Images

Figure HDA0005097391640000011 
Figure HDA0005097391640000012 
Figure HDA0005097391640000013
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a silver bismuthate / bismuth molybdate heterojunction photocatalyst rich in oxygen vacancies. Background Art
[0002] In recent years, with the development of economy, the demand for energy and resources has been increasing day by day, which has further led to the sharp contradiction between social development and resource scarcity. Therefore, the rational development and utilization of new energy has naturally become a hot topic. As a relatively clean energy, solar energy can not only convert solar energy into chemical energy, but also has a wide range of applications in water and air treatment, construction, environmental protection and chemical production. Especially in the field of semiconductor photocatalytic technology, it is mainly used in nitrogen fixation, carbon dioxide reduction, pollutant degradation, photocatalytic water decomposition, organic synthesis and sterilization. Semiconductor nanomaterials have certain effects in reducing heavy metal ions and degrading pollutants in water bodies, but due to their low efficiency, they are still not popular in daily use. Studies have shown that the main factors hindering the application of semiconductor materials in the field of photocatalysis are low visible light absorption efficiency, low photogenerated carrier migration efficiency and low interface reaction efficiency.
[0003] Bismuth molybdate (Bi2MoO6) consists of tetrahedral ion layers [Bi2O2] 2+ With octahedral ion layer [MoO4] 2- As the simplest semiconductor material in the family of oxygen-containing salts, it has important potential application value in photocatalysis due to its unique physicochemical properties and high visible light response performance. Since Yu discovered in 2005 that two-dimensional Bi2MoO6 nanosheets have good photocatalytic oxygen production activity, Bi2MoO6 has been used as an effective visible light photocatalyst to catalyze the degradation of organic pollutants in water and has become a research hotspot for new visible light photocatalysts. However, although single Bi2MoO6 has the characteristics and advantages of a good visible light response range, the recombination of photogenerated electrons and holes is also easier due to the small band gap, which reduces the quantum efficiency of this type of material and limits its degradation efficiency of organic pollutants. Therefore, it is necessary to further improve and improve the visible light photocatalytic activity of Bi2MoO6 through modification.
[0004] Silver-based semiconductor materials have become candidate materials for photocatalytic technology due to their unique crystal structure. Silver bismuthate (AgBiO3) has attracted much attention due to its controllable release of lattice oxygen, which produces a large amount of reactive oxygen species (ROS) in the absence of light. Silver bismuthate is a black crystal with a narrow band gap width and a special crystal structure. It has the characteristics of high stability, good catalytic performance, high visible light utilization, and strong redox properties. It is considered to be a semiconductor material with excellent performance. Compared with traditional catalysts, it has better photocatalytic activity and photocatalytic effect, can effectively remove organic pollutants in water, and has good application value. However, as far as single-component semiconductor materials are concerned, silver-based photocatalysts are prone to photocorrosion under visible light, and bismuth-based photocatalysts have the characteristics of low photogenerated carrier separation efficiency, which will reduce the stability and activity of this catalyst in degrading pollutants.
[0005] In response to a series of problems faced by the above photocatalysts in practical applications, AgBiO3 and Bi2MoO6 materials can be compounded, and the structural characteristics of bismuth molybdate itself can be utilized to prepare a modified AgBiO3 / Bi2MoO6 composite material, thereby improving the low efficiency of photogenerated carrier separation in the Bi2MoO6 material itself, thereby improving its photocatalytic activity.
[0006] Therefore, this study mainly focuses on the z-type heterojunction synthesized by Bi2MoO6 photocatalyst and silver bismuthate, and explores the catalytic activity of the heterojunction photocatalyst. Summary of the invention
[0007] In view of the shortcomings of the existing technology, the present invention conducts research on the z-type heterojunction synthesized by Bi2MoO6 photocatalyst and silver bismuthate, proposes a preparation method of silver bismuthate / bismuth molybdate heterojunction rich in oxygen vacancies, and explores the catalytic activity of the heterojunction photocatalyst.
[0008] The technical solution adopted by the present invention is: A method for preparing a silver bismuthate / bismuth molybdate heterojunction rich in oxygen vacancies, wherein a Bi2MoO6 nanomaterial with oxygen vacancies and an AgBiO3 nanomaterial are constructed into a staggered Z-type heterojunction to synthesize an AgBiO3 / Bi2MoO6 heterojunction photocatalytic material rich in oxygen vacancies.
[0009] The method for preparing the silver bismuthate / bismuth molybdate heterojunction rich in oxygen vacancies comprises the following steps: Step S1: Add 1.8 g of Bi2MoO6 powder into 50 ml of deionized water and continue ultrasonic treatment for 10 minutes; Step S2: Add 0.5 mmol of AgNO3 to the container, continue ultrasonication for 30 minutes, add the same molar amount of NaBiO3 as that of AgNO3 to the solution, and stir at 25°C for 15 minutes to obtain a solid product; Step S3: The obtained solid product was washed with deionized water and anhydrous ethanol respectively, and finally dried in a vacuum drying oven at 60° C. for 24 hours to complete the preparation of the AgBiO3 / Bi2MoO6 heterojunction.
[0010] In the method for preparing the oxygen vacancy-rich silver bismuthate / bismuth molybdate heterojunction, in step S1, the preparation process of Bi2MoO6 powder is as follows: Step S1.1: 1 mol Bi(NO3)3•5H2O and 0.14 mol (NH4)6MoO 24 •4H2O is dissolved in 40ml of ethylene glycol and stirred magnetically until dissolved; Step S1.2: Add 0.5-3 g PVP to the solution in step S1.1, adjust the pH value to 7, and continue stirring for 30 minutes; Step S1.3: transfer the solution obtained in step S1.2 into a 100 ml polytetrafluoroethylene-lined stainless steel hydrothermal reactor and react at 180° C. for 12 hours; Step S1.4: Cool to room temperature, filter and separate, and wash with deionized water and anhydrous ethanol to obtain a solid precipitate; Step S1.5: drying the obtained solid precipitate at 60°C for 24 hours to obtain Bi2MoO6 powder; Step S1.6: The obtained solid precipitate is calcined at 400°C in a N2 atmosphere for 12 hours to obtain Bi2MoO6 powder with oxygen vacancies.
[0011] The preparation method of the oxygen vacancy-rich silver bismuthate / bismuth molybdate heterojunction and the AgBiO3 / Bi2MoO6 heterojunction nano-photocatalytic material, wherein the mass fraction of AgBiO3 is 5-15%.
[0012] The method for preparing the oxygen vacancy-rich silver bismuthate / bismuth molybdate heterojunction, wherein AgBiO3 is a flower-like structure, Bi2MoO6 is a flake-like structure, and the flower-like AgBiO3 is dispersed in the flake-like Bi2MoO6.
[0013] The method for preparing the oxygen vacancy-rich silver bismuthate / bismuth molybdate heterojunction, wherein the mass fraction of AgBiO3 in the heterojunction nano-photocatalytic material is 10%.
[0014] In the method for preparing the oxygen vacancy-rich silver bismuthate / bismuth molybdate heterojunction, in step S1.2, the amount of PVP added is 0.5 to 3 g.
[0015] Beneficial effects of the invention: 1. The preparation method of silver bismuthate / bismuth molybdate heterojunction photocatalytic material rich in oxygen vacancies of the present invention combines Bi2MoO6 and AgBiO3 to form a heterojunction for the first time. Bi2MoO6, as a bismuth oxide, exhibits responsiveness to visible light due to its energy band structure, which improves the photocatalytic performance of the material. For the AgBiO3 / Bi2MoO6 heterojunction, the Bi2MoO6 bandgap is about 2.8 eV, and the AgBiO3 bandgap is about 0.8 eV. Both can be excited under visible light, and a staggered Z-type heterojunction can be formed, which is conducive to the rapid separation of photogenerated electron-hole pairs and improves the photocatalytic performance of the material.
[0016] 2. The preparation method of silver bismuthate / bismuth molybdate heterojunction photocatalytic material of the present invention comprises preparing a mixed solution with deionized water and ethylene glycol, and then sequentially adding Bi(NO3)3·5H2O and (NH4)6MoO 24 •4H2O, and ultrasonic dispersion. The introduction of ethylene glycol and PVP in this scheme has a reducing effect. At the same time, Bi2MoO6 containing oxygen vacancies was prepared by calcination at 400°C under N2 protection. The formation of oxygen vacancies is conducive to the improvement of the photocatalytic performance of the material. Oxygen vacancies (OVs) technology can optimize the band gap width of semiconductors and promote the effective separation of photogenerated electrons and holes, and is widely studied and adopted. OVs have a great influence on the electronic structure and physical properties of semiconductors, can reduce the band gap width of semiconductors, and improve visible light response. In addition, OVs can also generate a large number of local electrons on the surface of photocatalysts, increasing the adsorption and photocatalytic reaction active sites.
[0017] 3. The AgBiO3 / Bi2MoO6 heterojunction photocatalytic material synthesized by the preparation method of the present invention can construct and adjust the band structure of Bi2MoO6, so that its photocatalytic degradation performance is significantly improved, and the problems of low visible light utilization, low photogenerated electron-hole separation efficiency, and easy recombination of the photocatalytic material are effectively solved.
[0018] AgBiO3 / Bi2MoO6 heterojunctions were prepared by solvothermal method, and the structure and morphology of the materials were characterized by SEM and XRD. The results of visible light photocatalytic degradation of RhB showed that the prepared series of AgBiO3 / Bi2MoO6 heterojunctions had a significant effect on RhB (40 mL, 10 mg·L -1) are all higher than those of pure Bi2MoO6, among which the ABM-10 heterojunction has the strongest photocatalytic activity, with a degradation rate of 72% for RhB, which is 1.38 and 1.44 times that of pure Bi2MoO6 and pure AgBiO3, respectively. In addition, the ABM-10 heterojunction has good photocatalytic performance for several other polluted wastewaters (ciprofloxacin: 70%, phenol: 61%, methylene blue: 66%, methyl orange: 93%).
[0019] 4. The present invention proposes a simple, green, safe and low-cost method for preparing silver bismuthate / bismuth molybdate heterojunction photocatalytic materials rich in oxygen vacancies. The synthesis process is simple, the reaction conditions are mild, and no large-scale synthesis equipment is required; the reagents required for the synthesis are all conventional reagents with low toxicity and low cost. The prepared photocatalyst is efficient and stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Shown are electron microscope images of AgBiO3 (a), Bi2MoO6 (b) and ABM-10 (c) heterojunctions; Figure 2 Shown are the XRD spectra (a) and EPR spectra (b) of the synthesized materials; Figure 3 Shown is the high-resolution transmission spectrum of ABM-10; the ABM-10 heterojunction was further studied by TEM (a) and HRTEM (b); Figure 4 EDS-mapping spectrum of ABM-10 heterojunction shown (a) ABM-10 heterojunction electron microscope image, (b) O element, (c) Mo element, (d) Bi element, (e) Ag element, (f) element analysis, (g) EDS spectrum; Figure 5 (ab) are the degradation efficiency of the synthetic materials, (c) is the kinetic curve of RhB degradation and (d) is the absorption spectrum of RhB degradation over time; Figure 6 (a) shows the degradation efficiency of ABM-10 on different organic pollutants; (b) shows the 4-cycle experiment of ABM-10 degrading RhB; Figure 7 (a) shows the capture experiment of active species during the photodegradation of RhB, and (b) shows the capture experiment of DMPO-•O2 − and (c) EPR signal of DMPO-•OH. DETAILED DESCRIPTION
[0021] In order to make the technical concept and advantages of the present invention more clearly understood, the technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings. It should be understood that the following embodiments are only used to explain and illustrate the preferred implementation methods of the present invention, and should not be regarded as and do not constitute a limitation on the scope of patent protection claimed by the present invention. Example
[0022] The invention discloses a method for preparing a silver bismuthate / bismuth molybdate heterojunction rich in oxygen vacancies. The Bi2MoO6 nanomaterial with oxygen vacancies and the AgBiO3 nanomaterial are constructed into a staggered Z-type heterojunction to synthesize an AgBiO3 / Bi2MoO6 heterojunction photocatalytic material rich in oxygen vacancies. The AgBiO3 has a flower-like structure, the Bi2MoO6 has a sheet-like structure, and the flower-like AgBiO3 is dispersed in the sheet-like Bi2MoO6. The mass fraction of AgBiO3 is 5-15% relative to Bi2MoO6. Example
[0023] This embodiment is a method for preparing a silver bismuthate / bismuth molybdate heterojunction rich in oxygen vacancies, which comprises: Step 1: Bi(NO3)3•5H2O(1mol) and (NH4)6MoO 24 •4H2O (0.14 mol) was dissolved in 40 ml of ethylene glycol and stirred magnetically until dissolved; Step 2: Add 0.5-3 g PVP to the above solution, adjust the pH to 7, and continue stirring for 30 minutes; Step 3: The above solution was transferred to a 100 ml polytetrafluoroethylene-lined stainless steel hydrothermal reactor and reacted at 180°C for 12 hours; Step 4: Cool to room temperature, filter and separate, and wash with deionized water and anhydrous ethanol several times; Step 5: Dry the product at 60°C for 24 hours to complete the preparation of Bi2MoO6 powder; Step 6: Add 1.8 g of Bi2MoO6 powder to 50 ml of deionized water and continue ultrasonic treatment for 10 minutes using an ultrasonic machine; Step 7: Add 0.5 mmol of AgNO3, ultrasonicate for 30 minutes, add the same molar amount of NaBiO3 to the above solution, and stir at 25°C for 15 minutes; Step 8: The final product was washed three times with deionized water and anhydrous ethanol respectively, and finally dried in a vacuum drying oven at 60°C for 24 hours; Step 9: Calcine the obtained solid at 400°C for 12 hours in a N2 atmosphere to obtain Bi2MoO6 powder with oxygen vacancies. The preparation of the AgBiO3 / Bi2MoO6 heterojunction is completed. Example
[0024] The present embodiment is different from the embodiment 1 in that: (1) the mass fraction of AgBiO3 in the AgBiO3 / Bi2MoO6 nano-photocatalyst is 5% (denoted as ABM-5); (2) in step 7, the added amounts of AgNO3 and NaBiO3·2H2O are both 0.25 mmol. Example
[0025] The present embodiment is different from the embodiment 1 in that: (1) the mass fraction of AgBiO3 in the AgBiO3 / Bi2MoO6 nano-photocatalyst is 15% (denoted as ABM-15); (2) in step 7, the added amounts of AgNO3 and NaBiO3·2H2O are both 0.75 mmol.
[0026] Based on the oxygen vacancy-rich silver bismuthate / bismuth molybdate heterojunction prepared in Example 2, the catalytic activity of the heterojunction photocatalyst was investigated. Figure 1 SEM images of AgBiO3, Bi2MoO6 and AgBiO3 / Bi2MoO6 heterojunction.
[0027] from Figure 1 In (a), it can be seen that pure AgBiO3 is a flower-like structure composed of thin flakes with a diameter of about 1-2 µm. Figure 1 (b) Pure Bi2MoO6 presents a lamellar structure with a smooth surface. Figure 1 (c) shows the AgBiO3 / Bi2MoO6 heterojunction, showing flower-like AgBiO3 dispersed in the flake-like Bi2MoO6.
[0028] Figure 2 Shown are the XRD patterns (a) and EPR patterns (b) of the synthesized materials.
[0029] X-ray diffraction patterns of different samples were tested to investigate the composition of the materials. Figure 2 As shown in a, pure Bi2MoO6 exhibits obvious diffraction peaks at 2θ=28.3°, 32.5°, 33.1°, 36.0°, 47.1°, 55.4° and 56.3°, corresponding to the (131), (200), (060), (151), (260), (331) and (191) crystal planes of Bi2MoO6, respectively (JCPDS No.21-0102). After annealing in N2 atmosphere, except for the diffraction peak on the (060) plane, the peaks of Bi2MoO6 with oxygen vacancies do not change significantly, which may be due to the influence of oxygen defects. This is confirmed by EPR experiments ( Figure 2b). The obvious signal at g = 2.004 can verify the presence of oxygen vacancies in Bi2MoO6 due to electron capture by oxygen vacancies, which improves the photocatalytic activity. On the other hand, AgBiO3 exhibits characteristic diffraction peaks at 31.7° and 35.9°, which is consistent with the diffraction peaks of AgBiO3 (JCPDS No.89-9072). The characteristic diffraction peaks of AgBiO3 / Bi2MoO6 heterojunction containing oxygen vacancies are similar to those of Bi2MoO6, indicating that the heterogeneous crystalline structure of AgBiO3 / Bi2MoO6 is almost unaffected by AgBiO3. Due to the low content and dispersion of AgBiO3, no characteristic peaks of AgBiO3 were observed in the AgBiO3 / Bi2MoO6 heterojunction. No other impurity peaks were found in the product, indicating that a high-purity AgBiO3 / Bi2MoO6 heterojunction was formed.
[0030] Figure 3 Shown is a high-resolution projection map of ABM-10.
[0031] The ABM-10 heterojunction was further investigated by TEM and HRTEM. Figure 3 As shown in a, both AgBiO3 and Bi2MoO6 flakes are clearly visible, with diameters of about 1-3µm, and they are interlaced in the ABM-10 heterojunction. Figure 3 In b, the lattice spacings of 0.315 nm and 0.310 nm correspond to the (131) plane of Bi2MoO6 and the (104) plane of AgBiO3, respectively, which further confirms the formation of the AgBiO3 / Bi2MoO6 heterojunction.
[0032] Figure 4 The EDS-mapping spectrum of the ABM-10 heterojunction is shown. It shows that the elements Bi, O, Mo and Ag are detected on the surface of the AgBiO3 / Bi2MoO6 heterojunction.
[0033] Figure 5 (ab) are the degradation efficiency of the synthetic material, (c) is the kinetic curve of RhB degradation and (d) is the absorption spectrum of RhB degradation changing with time.
[0034] Wastewater generated by the printing and dyeing industry is not only difficult to treat, but also causes serious environmental pollution and endangers human health. Among them, rhodamine B (RhB) is the most common type, which is used as a target pollutant to evaluate the photocatalytic performance of the prepared samples. Figure 5As shown in a, under visible light irradiation for 100 minutes, the degradation efficiency of pure Bi2MoO6 and AgBiO3 for RhB is 52% and 50%, respectively. The degradation efficiency of Bi2MoO6-OVs for RhB is 57%, which is due to the introduction of oxygen vacancies, which can reduce the band gap width, promote the separation and transfer of photogenerated electrons and holes, and enhance the photocatalytic activity. The ABM-10 heterojunction has the best photocatalytic activity, with a degradation efficiency of 72%. Obviously, with the increase of AgBiO3 content, the degradation efficiency of the catalyst first increases and then decreases, indicating that AgBiO3 plays an important role in the photocatalytic degradation process, which is mainly due to the fact that AgBiO3 promotes charge transfer and inhibits the recombination of photoinduced electron and hole pairs. However, excessive AgBiO3 may form new recombination centers for photoinduced electrons and holes, reducing the photocatalytic activity. As Figure 5 As shown in b, in the absence of catalyst, the control blank showed slight degradation of RhB, and the experiment reached adsorption-desorption equilibrium in the dark 30 minutes before illumination. By comparison, the mechanical mixture of Bi2MoO6-OVs and 10 wt% AgBiO3 was also tested. The experimental results showed that the photocatalytic activity of the mechanical mixture was not as good as that of the ABM-10 heterojunction, indicating that the interface contact between AgBiO3 and Bi2MoO6-OVs in the mechanical mixture was poor. Figure 5 In c, the reaction kinetics of RhB degradation was modeled by a pseudo-first-order kinetic model: ln(C o / C) = kt , where C o and C are the initial and instantaneous concentrations at reaction time t, respectively, and k is the rate constant. The rate constant for the ABM-10 heterojunction is 0.0197 min -1 , while the k of ABM-5, ABM-15, AgBiO3, Bi2MoO6 and Bi2MoO6-OV are 0.0094, 0.0072, 0.0046, 0.0057 and 0.0066 min, respectively. -1 The k of ABM-10 heterojunction is 2.10, 2.73, 4.28, 3.46 and 2.98 times higher than that of ABM-5, ABM-15, AgBiO3, Bi2MoO6 and Bi2MoO6-OV. Figure 5 d shows the absorption spectrum of RhB degraded by ABM-10 heterojunction. Obviously, the characteristic peak of RhB at 570 nm gradually decreases, indicating that RhB is gradually degraded.
[0035] Figure 6 Figure a shows the degradation efficiency of ABM-10 on different organic pollutants; Figure b shows the 4-cycle experiment of ABM-10 degrading RhB. Figure 6In a, the degradation efficiencies of ABM-10 for RhB, CIP, MB, MO, LR5B, BPA, and phenol were 72%, 70%, 66%, 63%, 55%, 41%, and 37%, respectively. These different photocatalytic activities of ABM-10 are attributed to the different adsorption characteristics and molecular structures of these organic pollutants. The photocatalytic stability of the prepared samples is of great significance for practical applications. In order to study the stability of the ABM-10 heterojunction, four cycles of photocatalytic degradation of RhB were carried out. Figure 6 As shown in (b), after four consecutive cycles, the ABM-10 heterojunction still has excellent RhB degradation activity.
[0036] Figure 7 (a) shows the capture experiment of active species during the photodegradation of RhB, and (b) shows DMPO-•O2 − To study the photocatalytic mechanism of the ABM-10 heterojunction, isopropyl alcohol (IPA), disodium ethylenediaminetetraacetate (EDTA-2Na), and benzoquinone (BQ) were added to capture hydroxyl radicals (•OH), holes (h + ) and superoxide anion radicals (·O2 - ).
[0037] like Figure 7 As shown in a, after adding EDTA-2Na and benzoquinone to the reaction, the degradation efficiency of RhB was only 14% and 19%, respectively, indicating that the photodegradation process was severely inhibited. When IPA was added, the degradation efficiency of RhB was 56%, indicating that the degradation process was slightly inhibited. The results show that·O2 - and h + It is the main active species in the photocatalytic reaction, while •OH plays an important role in assisting the degradation.
[0038] In addition, we also performed EPR experiments to detect the O2 - and •OH. Figure 7 As shown in bc, in the dark, DMPO-•OH and DMPO-•O2 - No characteristic signals were observed. However, DMPO-•OH- and DMPO-•O2 were observed in ABM-10 after 10 minutes of illumination. - The signal further confirmed the existence of •OH and ·O2 in the photocatalytic process. - .
[0039] It can be seen that the AgBiO3 / Bi2MoO6 heterojunction photocatalytic material obtained by the photocatalytic material preparation method of the present invention can construct and adjust the band structure of Bi2MoO6, so that its photocatalytic degradation performance is significantly improved, and the problems of low visible light utilization, low photogenerated electron-hole separation efficiency, and easy recombination of the photocatalytic material are effectively solved.
Claims
1. A method for preparing a silver bismuthate / bismuth molybdate heterojunction rich in oxygen vacancies, characterized in that: Bi2MoO6 nanomaterials with oxygen vacancies and AgBiO3 nanomaterials were constructed into a staggered Z-type heterojunction to synthesize AgBiO3 / Bi2MoO6 heterojunction photocatalytic materials rich in oxygen vacancies.
2. The method for preparing the silver bismuthate / bismuth molybdate heterojunction rich in oxygen vacancies according to claim 1, characterized in that: The preparation process includes the following steps: Step S1: Add 1.8 g of Bi2MoO6 powder into 50 ml of deionized water and continue ultrasonic treatment for 10 minutes; Step S2: Add 0.5 mmol of AgNO3 to the container, continue ultrasonication for 30 minutes, add the same molar amount of NaBiO3 as that of AgNO3 to the solution, and stir at 25°C for 15 minutes to obtain a solid product; Step S3: washing the obtained solid product with deionized water and anhydrous ethanol respectively, and finally drying it in vacuum at 60° C. to obtain the AgBiO 3 / Bi 2 MoO 6 heterojunction photocatalytic material.
3. The method for preparing the silver bismuthate / bismuth molybdate heterojunction rich in oxygen vacancies according to claim 2, characterized in that: In step S1, the preparation process of Bi2MoO6 powder is as follows: Step S1.1: 1 mol Bi(NO3)3•5H2O and 0.14 mol (NH4)6MoO 24 •4H2O is dissolved in 40ml of ethylene glycol and stirred magnetically until dissolved; Step S1.2: Add 0.5-3 g PVP to the solution in step S1.1, adjust the pH to 7, and continue stirring for 30 minutes; Step S1.3: transfer the solution obtained in step S1.2 into a 100 ml polytetrafluoroethylene-lined stainless steel hydrothermal reactor and react at 180° C. for 12 hours; Step S1.4: Cool to room temperature, filter and separate, and wash with deionized water and anhydrous ethanol to obtain a solid precipitate; Step S1.5: drying the obtained solid precipitate at 60°C for 24 hours to obtain Bi2MoO6 powder; Step S1.6: The obtained solid precipitate is calcined at 400°C in a N2 atmosphere for 12 hours to obtain Bi2MoO6 powder with oxygen vacancies.
4. The method for preparing the silver bismuthate / bismuth molybdate heterojunction rich in oxygen vacancies according to claim 1, 2 or 3, characterized in that: The AgBiO3 / Bi2MoO6 heterojunction nano photocatalytic material, wherein the mass fraction of AgBiO3 is 5-15%.
5. The method for preparing the silver bismuthate / bismuth molybdate heterojunction rich in oxygen vacancies according to claim 3, characterized in that: AgBiO3 has a flower-like structure, Bi2MoO6 has a flake-like structure, and the flower-like AgBiO3 is dispersed in the flake-like Bi2MoO6.
6. The method for preparing the silver bismuthate / bismuth molybdate heterojunction rich in oxygen vacancies according to claim 3, characterized in that: In the heterojunction nano-photocatalytic material, the mass fraction of AgBiO3 is 10%.
7. The method for preparing the silver bismuthate / bismuth molybdate heterojunction rich in oxygen vacancies according to claim 3, characterized in that: In step S1.2, the amount of PVP added is 0.5 to 3 g.